ANALISIS PERAWATAN MESIN CNC YUNAN TOOL WORKS DENGAN METODE RCM PADA PT WILIS INDONESIA STEEL : ANALYSIS OF YUNAN TOOL WORKS CNC MACHINE MAINTENANCE USING THE RCM METHOD AT PT WILIS INDONESIA STEEL - Farrel Hartono; Saiful Arif; Devina Rosa (Mechanical Engineering Department Polinema Kediri, 2025)
This study analyzes the maintenance of the CY-K510N CNC machine at PT Wilis Indonesia Steel using the Reliability Centered Maintenance (RCM) method. The main issue identified is high downtime, primarily caused by repeated failures of the servo motor, which recorded 15 breakdowns and a total downtime of 218 hours in 2023. The RCM approach was chosen because it can identify critical components and develop maintenance strategies based on function and failure risk, unlike conventional preventive methods that rely only on fixed schedules. The Failure Mode and Effect Analysis (FMEA) results show that the servo motor and gear spindle are the most critical components with the highest risk values. Implementing the RCM strategy is recommended to improve machine reliability, reduce breakdown frequency, and enhance overall productivity.